2016
DOI: 10.1111/jbi.12761
|View full text |Cite
|
Sign up to set email alerts
|

Re‐defining the natural range of Scots Pine (Pinus sylvestrisL.): a newly discovered microrefugium in western Ireland

Abstract: Aim Native Pinus sylvestris became extirpated in Ireland, during a massive population decline experienced throughout Europe. It was extensively replanted in Ireland during the 18th century from Scottish stock. We test the hypothesis that P. sylvestris in Rockforest Co. Clare did not become extirpated during the P. sylvestris decline, and persisted to present day independent of 18th century plantations. Location Rockforest, Co. Clare in Ireland. Methods Fossil pollen was counted from a terrestrial core. Radioca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 43 publications
1
13
0
Order By: Relevance
“…These findings are also supported by those of McGeever and Mitchell's [64] analysis of a radiocarbon-dated terrestrial core from Aughrim Swamp, which is located 650 m north-east of the Rockforest Lough coring site (Figure 1). Pollen preservation was good throughout the pollen profile, which extends from the present to 1600 cal BP/AD 350.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…These findings are also supported by those of McGeever and Mitchell's [64] analysis of a radiocarbon-dated terrestrial core from Aughrim Swamp, which is located 650 m north-east of the Rockforest Lough coring site (Figure 1). Pollen preservation was good throughout the pollen profile, which extends from the present to 1600 cal BP/AD 350.…”
Section: Discussionsupporting
confidence: 78%
“…However, analyses of fossil stomata provided unambiguous evidence of local presence of P. sylvestris when Pinus pollen frequencies were as low as 2.8% [62] and 0.4% [63]. From a study of modern pollen deposition in the Rockforest area, McGeever and Mitchell [64] concluded that a Pinus pollen value of 5% indicated local presence of P. sylvestris in this area. The Pinus curve from Rockforest Lough is consistently high, never less than 38.2%, and greatly exceeds the critical pollen percentages.…”
Section: Discussionmentioning
confidence: 99%
“…As regards the Gortlecka profile from near Rockforest, there are considerable uncertainties associated with the dating that are not alluded to, though these uncertainties were referred to in the initial publication (Watts 1984). Interestingly, a short unpublished pollen diagram by Coleman (1978) from Gortboyheen Lough in the northern central Burren (SM-F2; see pollen assemblage zones 2-4) has similarities to that published by McGeever and Mitchell (2016). Local survival of Scots pine at Gortboyheen is not, however, regarded as likely for various reasons including that there are no known records for the local presence of pine.…”
Section: Fossil and Surface-pollen Data From Aran: Implications For Imentioning
confidence: 94%
“…The two short pollen profiles that have been published suggest rather different local histories of pine. Furthermore, the published 14 C dates from Killarney and the Burren, that have been drawn on by McGeever and Mitchell (2016) to support their arguments, are inappropriate. The 14 C date cited from the northern Burren (Lios Láirthín Mór), for instance, relates to a profile that does not include the final pine decline (Jeličić and O'Connell 1992).…”
Section: Fossil and Surface-pollen Data From Aran: Implications For Imentioning
confidence: 99%
“…While this demise was sudden in places, an increasing body of research has demonstrated that the timing and nature of this event are far from uniform (Blackford et al, 1992; Edwards et al, 1996; Edvardsson et al, 2016; Hall et al, 1994, 1996; Lageard et al, 1999, Payne et al, 2013). The decline has been attributed to various factors including climatic deterioration, increased competition with other tree species, anthropogenic effects, pathogens and volcanic activity (Bennett, 1984, 1995; Blackford et al, 1992; Hall et al, 1996; Manning et al, 2010; McGeever and Mitchell, 2016).…”
Section: Introductionmentioning
confidence: 99%